Kinetics of long-lived luminescence of eosin in Langmuir-Blodgett films - Ibraev, N. Kh.; Zhunusbekov, A. M. (Nauka/Interperiodica, 2002)
The spectral and kinetic properties of photoluminescence of mixed Langmuir–Blodgett (LB) films of eosin decyl ether and palmitic acid on a solid substrate are studied. The electronic absorption and fluorescence spectra of the films are identical to the spectra of the dye in ethanol. An increase in the dye concentration in a monolayer results in the appearance of a dimer absorption band, quenching of fluorescence of monomers, and the red shift of the spectral bands. At 90 K, the distinct phosphorescence and delayed fluorescence bands of LB films were observed. The decay kinetics of phosphorescence and delayed fluorescence is nonexponential. It is shown that the decay curve of delayed fluorescence is determined by triplet–triplet annihilation (TTA) and T1S1 triplet–singlet intersystem crossing (IS). The initial nonexponential phosphorescence decay is caused the dominant contribution of TTA to the decay of triplet molecules. The experimental data are interpreted based on the mechanisms of exchange–resonance and inductive–resonance annihilation.